Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-03T17:11:33+01:00
A) 1,2 - 1,9x = 0,5 (x + 3) - 0,3 (x + 5)
1,2-1,9x= 0,5x+1,5-0,3x-1.5
-1,9x-0,5x+0,3x=-1,2+1,5-1,5
-2,1x=-1,2/(-2,1)
x okolo 0,58

b) 5/6 (y - 4) - 1/3 = 1/4 (y + 5) + 1/2
5/6y -5-1/3=1/4y+1 i 1/4 +1/2
5/6y-1/4y=1 i 1/4+1/2+5+1/3
10/12y-3/12y=1 i 3/12 +6/12+5+4/12
7/12y= 6 i 13/12
7/12y-85/12/; 7/12
y=85/12*12/7
y=12 i 1/12
21 3 21
2010-03-03T17:20:23+01:00
A) 1,2 - 1,9x = 0,5x + 1,5 - 0,3x - 1,5 ( 1,5 sie skróci)
-1,9x - 0,5x + 0,3x = 1,2
2,4x + 0,3x = 1,2
2,7x = 1,2 / : 2,7
x = 0, 44444444...
x = 0,(4)
b) 5/6y - 3 1/3 - 1/3 = 1/4y + 1 1/4 + 1/2
5/6y - 1/4y = 1 1/4 + 1/2 + 3 1/3 + 1/3
7/12y = 5 5/12 / : 7/12
y = 9 2/7
7 4 7